111 Improved Functional Outcomes of Stroke Patients Undergoing Mechanical Thrombectomy After Arriving via Mobile Stroke Unit. (April 2023) - Al Saiegh, Fadi; Velagapudi, Lohit; Khanna, Omaditya; Tjoumakaris, Stavropoula I.; Gooch, M. Reid; Rosenwasser, Robert H.; Jabbour, Pascal
Abstract : INTRODUCTION: Mobile stroke units (MSUs) have been implemented worldwide for stroke care, but outcome data is lacking to show their efficacy specifically in patients undergoing mechanical thrombectomy (MT). METHODS: A retrospective review of a stroke database was performed to identify patients who underwent MT after arrival via MSU from August 2019 to December 2020. Demographic factors, past medical history, stroke characteristics, treatment variables, complications, and functional outcomes were recorded. These were compared to date-matched patients who underwent MT after arrival via conventional means. RESULTS: Seven patients were treated with MT after arriving by MSU. These were compared to 50 date- matched patients who underwent thrombectomy after arrival through conventional means. No statistically significant difference between cohorts was observed in terms of demographic variables, co-morbidities, stroke characteristics, or tPA administration. Patients from the MSU cohort had significantly shorter time from symptom onset to groin puncture time (191.33 mins ± 77.53 vs 483.51 mins ± 322.66, p = 0.034). Importantly, MSU-transferred patients had significantly better discharge functional status measured by modified Rankin Scale (mRS) (1.86 ± 1.35 vs 3.57 ± 1.88, p = 0.024). No significant difference in final TICI score, complications, length of stay, or mortality was observed. CONCLUSIONS: Our pilot study demonstrates the efficacy of the MSU in decreasing door-to-puncture time and a concordant improvement in discharge mRS. Further prospective studies are needed to assess cost-efficacy and optimal protocol for MSUs in stroke care.